(untitled) (Medical Forum Monthly, 2024)
Objective: To explore the significance of pathological and biomarker changes in response to neoadjuvant chemotherapy in terms of disease free survival and overall survival in Pakistani population. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Department of Oncology, Liaquat National Hospital from January 2004 to January 2011. Materials and Methods: A total of 104 patients with locally advanced breast carcinoma (inoperable) were included in the study retrospectively who had received neoadjuvant chemotherapy followed by surgery. Results: Out of the 104 patients who completed chemotherapy and underwent surgery, 19 (14.4%) had complete pathological response (pCR), 47 (35.6%) had node negative residual disease (NNRD), and 38 (28.8%) had node positive residual disease (NPRD). Factors associated with better 2 year overall survival included pCR, NNRD, post-chemotherapy unchanged positive hormonal status and post chemotherapy changed from negative to positive hormonal status, prechemotherapy Ki-67 <20 % as well as Ki-67 score of >20% changed to less than 20% post chemotherapy. Factors associated with less chances of recurrence were NNRD, unchanged hormone positive and change from hormone negative to hormone positive. Prechemotherapy HER2Neu positive had higher chances of recurrence. Patients with more than 20% pre-chemotherapy Ki-67 had 8.3 times higher chances of recurrence than those with less than 20%. Conclusion: We concluded that 2yrs overall survival in patients who received neoadjuvant chemotherapy were significantly associated with cPR, NNRD, unchanged positive hormonal status, and post chemo changed from –ve to +ve hormonal status, prechemo ki67 <20% as well as ki67 score of >20% changed to less than 20% post chemotherapy. Factors associated with less chances of recurrence were pCR, node negative residual disease, unchanged hormone +ve and change from hormone –ve to +ve disease.